Application of the passive control of shock wave to the reduction of high-speed impulsive noise. (2nd March 2011) - Doerffer, Piotr; Szulc, Oskar
Strong, normal shock wave, terminating a local supersonic area on an airfoil (or helicopter blade), not only limits aerodynamic performance but also becomes a source of a high-speed impulsive (HSI) noise. The application of a passive control system (a cavity covered by a perforated plate) on a rotor blade should reduce the noise created by a moving shock. This article covers details of the numerical implementation of the Bohning/Doerffer transpiration law into the SPARC code and includes a validation against the experimental data obtained for the ONERA transonic nozzle with a flat wall. The passive control device is then applied numerically on a helicopter blade in high-speed transonic hover conditions to weaken the shock wave – the main source of HSI noise.